Kyai Abd. Rachman Bin Sopa Hamid: Jejak Keluarga Kesultanan Palembang Darussalam Di Tulung Selapan Ogan Komering Ilir - Pria Harapan; Otoman (Tanjak: Sejarah dan Peradaban Islam, 2024)
This research is the result of historical research with the title " Kyai Abd. Rachman Bin Sopa Hamid: Palembang Darussalam Sultanate Family in Tulung Selapan Ogan Komering ". This research was conducted to determine the journey and role of Kyai Abd. Rachman Bin Sopa Hamid in Tulung Selapan through the historical evidence left behind. In this research, Levinson's Role Theory is used. Through this theory, the traces, role and position of Kyai Abd can be analyzed. Rachman Bin Sopa Hamid in the Tulung Selapan village community, Ogan Komering Ilir Regency during the Palembang Darussalam Sultanate era until its current influence on the local community. Apart from that, the research method used is descriptive qualitative. From the results of his research, it is known that the fall of the Palembang sultanate into Dutch hands was marked by the capture of Sultan Mahmud Badaruddin II and his family who were then exiled to Ternate (North Maluku). At the same time, several imperial families and other Mujahid figures also fled to other areas, including Kyai Abdurachman bin Sopa Hamid, who at the time also fled to the Ogan Komering Ilir area, precisely in Tulung Selapan, until he died. The whereabouts of Kyai Abd. Rachman Bin Sopa Hamid in Tulung Selapan is marked by the presence of several relics in the form of a collection of swords and tenongs as well as the existence of Kyai Abd's food. Rachman Bin Sopa Hamid. During his escape in Tulung Selapan, Kyai Abdurachman bin Sopa Hamid then preached and broadcast the Islamic religion through education to the local community so that he was also known as a cleric and played a major role in politics such as leading the local community in facing the Dutch colonialists who came to Tulung Selapan to this day